G308(P) Sudden unexpected death in epilepsy (sudep) during sleep in three 17-year-old adolescents without intellectual disability. (12th March 2018) - Lim, A; Ramesh, V; Annavarapu, S; Polvikoski, T
Abstract : Aim: To report risk factor(s) that might have led to SUDEP in three similar cases. Methods: Case note reviews; post-mortem reports; interviews with bereaved guardians/parents. Results: 17-year-old male had juvenile-onset generalised epilepsy diagnosed with onset at age 15. His generalised tonic-clonic seizures (GTCS) were mainly nocturnal; controlled with Valproate and Leveteracetam. His father saw playing on his computer at 1030 pm and was found dead in his bedroom floor in early morning. No structural brain lesion demonstrated on postmortem except incidental right temporal pole arachnoid cyst. 17-year-old male with generalised epilepsy epilepsy with febrile seizures (GEFS+) with onset at age 2. His GTCS were relatively infrequent and only during intercurrent illness and had been treated with Valproate. He had been playing videogames throughout the night and went to bed the following evening. He was found dead at 930 pm face down in his bed. 17-year-old female had presented with first episode of GTCS secondary to previously undiagnosed autoimmune hypothyroidism at age 15. Her Hashimoto encephalopahty was treated with steroids and thyroxine. After the initial presentation, no GTCS were reported. She was on thyroxine with no anti-epileptics. She had headache the day before. She was found dead face down in her bed in the early morning. Discussion: SUDEP typically affects 1 in 4500 children. Risk factors for SUDEP are young age, male sex, early onset, GTCS, and being in bed. Sodium channel mutation epilepsies are an at risk group for SUDEP. In this review, all three patients were aged 17 years and manifested only GTCS of varying aetiology. They had no intellectual disability or known poor compliance. All had been asleep in bed prior to SUDEP. Conclusions: All three adolescents were sleep-related SUDEP. Potential strategies for prevention include avoiding sleep deprivation, counselling adolescents with sodium channel epilepsies and considering nocturnal seizure detection device.